Modelo Para Avalia??o de Modula??es Digitais na Faixa de Ondas Milim?tricas - Reis, Tiago Magalh?es dos (2018)
The use of millimeter waves in wireless communication systems paves the way for solving the problem of spectrum scarcity currently experienced in lower frequencies, yet allowing for higher bit rates. However, impairments that are not of major importance in lower frequencies become relevant in the millimeter wave range, for instance the high signal attenuation and hardware impairments like phase noise, I-Q imbalance, and amplifier nonlinearities. In this dissertation, recent models proposed in the literature for such impairments are combined in a new model for assessing the performance of digital modulations. The proposed model is then applied to the performance analysis of the M-ary frequency-shift keying (MFSK) modulation with non-coherent detection, and to the M-ary phase-shift keying (MPSK) and M-ary quadrature amplitude modulation (MQAM) with coherent detection. The results brought out the different degrees of robustness of these modulations to the modeled impairments, highlighting the attractiveness of the MFSK and the 16QAM modulations. Moreover, it is unveiled that the MFSK is not always a robust solution, contrasting with recent claims in the literature.